Neurotoxic and neuroprotective effects of homocysteine and hydrogen sulfide - G.F. Sitdikova; A. Hermann; A.V. Yakovlev (Учёные записки Казанского университета: Серия Естественные науки)
Homocysteine is a sulfhydryl-containing amino acid derived from methionine. The cellular concentration of homocysteine is regulated by two key pathways: remethylation back to methionine or transsulfuration to cysteine with simultaneous production of hydrogen sulfide (H2S). Homocysteine levels increase in different conditions, including genetic factors, diet, life style or miscellaneous medication. Elevated levels of the homocysteine, called hyperhomocysteinemia (hHcy), are associated with a higher risk of neurovascular diseases, dementia, developmental impairments or epilepsy. Oxidative stress is one of the common mechanisms of homocysteine-induced disorders. H2S as an established gasotransmitter implicated in the regulation of numerous physiological functions is also well-known for its neuroprotective potential. The recent data indicate that the level of H2S decreases in hHcy conditions, which may mediate homocysteine-induced neurotoxicity. This review summarizes the available data on homocysteine and H2S metabolism and mechanisms of H2S mediating neuroprotection and can be helpful in searching for ways to prevent homocysteine-induced neurotoxicity.